1999
DOI: 10.1038/6986
|View full text |Cite|
|
Sign up to set email alerts
|

Spliceosome-mediated RNA trans-splicing as a tool for gene therapy

Abstract: We have developed RNA molecules capable of effecting spliceosome-mediated RNA trans-splicing reactions with a target messenger RNA precursor (pre-mRNA). Targeted trans-splicing was demonstrated in a HeLa nuclear extract, cultured human cells, and H1299 human lung cancer tumors in athymic mice. Trans-splicing between a cancer-associated pre-mRNA encoding the beta-subunit of human chorionic gonadotropin gene 6 and pre-trans-splicing molecule (PTM) RNA was accurate both in vitro and in vivo. Comparison of targete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
170
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(178 citation statements)
references
References 38 publications
3
170
0
Order By: Relevance
“…215 Spliceosome-mediated RNA trans-splicing (SMarT) is another method for mRNA reprogramming, and has been tested in tau transfected cells. 216,217 Trans-splicing occurs between the 5= splice site of a pre-mRNA and the 3= splice site of a second mRNA at the spliceosome. With SMarT, the endogenous target pre-mRNA becomes trans-spliced to an exogenously delivered pre-transsplicing molecule.…”
Section: Isoform Approachesmentioning
confidence: 99%
“…215 Spliceosome-mediated RNA trans-splicing (SMarT) is another method for mRNA reprogramming, and has been tested in tau transfected cells. 216,217 Trans-splicing occurs between the 5= splice site of a pre-mRNA and the 3= splice site of a second mRNA at the spliceosome. With SMarT, the endogenous target pre-mRNA becomes trans-spliced to an exogenously delivered pre-transsplicing molecule.…”
Section: Isoform Approachesmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] We are developing a technology called spliceosome mediated RNA trans-splicing (SMaRT) to take advantage of the cell's endogenous splicing machinery as a strategy for modifying pre-mRNA. 10 The SMaRT process uses pretherapeutic RNA molecules (PTMs) that are designed to base pair with the intron of a targeted pre-mRNA to suppress target cis-splicing while enhancing trans-splicing between the PTM and target. A potential application for SMaRT involves repairing mutant pre-mRNA molecules associated with genetic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with observations in a previously reported study, which concluded that the presence of the safety molecule was associated with reduced trans-splicing efficiency. 28 In conclusion, we have shown that our ATMs can specifically target and trans-splice DMPK pre-mRNA. Although the amount of trans-splicing achieved was not high, the findings offered support for the potential of trans-splicing as a novel therapeutic strategy in myotonic dystrophy.…”
Section: Exon 15 Mcsmentioning
confidence: 63%
“…28 In our study, we included this safety molecule in four of the eight ATMs. We observed only a single specific trans-spliced RT-PCR product with ATMs with the safety molecule.…”
Section: Exon 15 Mcsmentioning
confidence: 99%